2015
DOI: 10.7439/ijbr.v6i1.1575
|View full text |Cite
|
Sign up to set email alerts
|

Bakers Cyst: A Case Report and its clinical significance

Abstract: The Baker's or Popliteal cyst is a bursa seen between medial head Gastrocnemius and Semimembranosus. This bursa when present usually communicates with the cavity of Knee joint, most of the times being asymptomatic. They can occur due to any intra-articular pathology including bony inflammation, cartilaginous lesions, meniscal or ligament tear, etc. The symptomatic cases are mainly leading to pressure effects due to anatomical vulnerability of surrounding structures. Symptoms related to Popliteal vein compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…BCs or popliteal cysts are bursal enlargements between the medial head of the gastrocnemius and semimembranosus. 5 They are formed by overfilling and distension of the gastrocnemius-semimembranosus bursa with synovial fluid through a communication with the knee joint capsule. 6 They may also be formed by herniation of the synovial membrane through the joint capsule.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BCs or popliteal cysts are bursal enlargements between the medial head of the gastrocnemius and semimembranosus. 5 They are formed by overfilling and distension of the gastrocnemius-semimembranosus bursa with synovial fluid through a communication with the knee joint capsule. 6 They may also be formed by herniation of the synovial membrane through the joint capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal cyst rupture into the soft tissue of the thigh has also been reported. 26 DUS & MRI avoids misdiagnosis and inappropriate treatment, 5 [Triveda S et al 2015], with some authors considering DUS the imaging of choice. 27 Kim et al 2014, concluded that DUS differentiated purely cystic masses from more solid lesions and could exclude a DVT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation

Quiste de Baker gigante. Presentación de un caso

Dryjanski Lerner,
Rodríguez Rodríguez,
Trueba Vasavilbaso
et al. 2024
Ortho-Tips